PEDAGOGICAL AND PSYCHOLOGICAL ASPECTS OF PROFESSIONAL ADAPTATION OF FUTURE TEACHERS - avezova, nigora (Центр Научных Публикаций (buxdu.uz), 2021)
Abstract - the article provides information about the pedagogical and psychological aspects of professional adaptation of future teachers. The impacts of changes in society on professionals, the specifics of their professional adaptation are also discussed. However, the pedagogical and psychological aspects were analyzed using examples. It also covers the modern requirements for the professional knowledge and personal qualities of professionals.